Apical microsurgery vs repeated orthograde treatment of root canals: criteria for selection of a method of treatment. Part II - M. V. Berkhman; S. S. Kozlov; A. I. Prosin; O. V. Chernenko (Эндодонтия Today)
Relevance. In case of failure of primary therapy of root canals the modern endodontiya gives to doctors various opportunities of treatment allowing to avoid a tooth extraction. In article the reasons of failure of standard endodontic treatment are considered.Aim. Recommendations and diagnostic criteria for the choice of a technique of repeated intervention are discussed: orthograde therapy, apical surgical treatment, a tooth extraction or dynamic observation of a clinical situation. The clinical cases in article illustrate process of making decision on the choice of tactics of treatment in various clinical situations.